Emerging roles of PLCγ1 in endothelial biology - Chen, Dongying; Simons, Michael (Science signaling, 2021)
Phospholipase C γ1 (PLCγ1) is a member of the PLC family that functions as signal transducer by hydrolyzing membrane lipid to generate second messengers. The unique protein structure of PLCγ1 confers a critical role as a direct effector of VEGFR2 and signaling mediated by other receptor tyrosine kinases. The distinct vascular phenotypes in PLCγ1-deficient animal models and the gain-of-function mutations of PLCγ1 found in human endothelial cancers point to a major physiological role of PLCγ1 in the endothelial system. In this review, we discuss aspects of physiological and molecular function centering around PLCγ1 in the context of endothelial cells and provide a perspective for future investigation.